Closing the Gap Between the Coral Sea and the Equator: Direct Observations of the North Australian Western Boundary Currents. Issue 12 (19th December 2018) - Ridgway, Ken R.; Benthuysen, Jessica A.; Steinberg, Craig
Abstract: Boundary currents along northeastern Australia provide source waters for the East Australian Current and redistribute water to the equator within the Gulf of Papua Current (GPC). These currents are formed following the bifurcation of two Coral Sea westward jets, the North Vanuatu Jet (NVJ) and the North Caledonian Jet. While the existence of the boundary currents has been inferred from limited geostrophic sections, gridded climatological analyses, and modeling studies, no direct measurements have been collected. This study synthesizes current and water property measurements from a 7‐year record at Lizard Island and multiple Seaglider deployments between 2010 and 2014. Both repeat glider transects at 14.5 and 18°S and deployments spanning latitudes between 18 and 11°S are included. Cross‐track velocities of these currents show their vertical structure, seasonal changes, and the spatial translation of the bifurcation latitude. The NVJ bifurcation varies seasonally about a mean latitude between 14.4 and 14.7°S. It has a peak northward extent in summer, when the East Australian Current and GPC exhibit maximum and minimum transports, respectively. The deeper GPC originates from the North Caledonian Jet south of 18°S and varies seasonally by 4 Sv. When the westward flow of the NVJ reaches the boundary, the GPC's northward transport grows by ~13 Sv. The salinity signature of the glider data confirms that up to 6 Sv of this influx is sourced from the base of the NVJ. The observed seasonal cycle of current strength and changes in along boundary transport are consistent with the results from an ocean general circulation model. Plain Language Summary: We use a set of ocean glider observations and a current meter mooring to describe the behavior of the currents along the north Queensland coast of Australia. These are the first direct measurements of these currents. These boundary flows are formed after westward currents flowing through the Coral Sea, reach the boundary, and are either turned to the equator (Gulf of Papua Current, GPC) or to the pole (East Australia Current, EAC). In the surface layer, the junction point varies seasonally about a mean latitude in the range 14.4–14.7°S. It has a peak northward extent in summer, when the EAC and GPC exhibit maximum and minimum transports, respectively. About a half of the deeper GPC component originates from south of 18°S with the remainder being added at the shallow junction point. South of this point the strong EAC summer flow leads to a net full‐depth flow toward the pole. Key Points: The mean upper thermocline North Vanuatu Jet (NVJ) bifurcation is just south of 14.4°S The equatorward Gulf of Papua Current is augmented by 13 Sv from the NVJ including 6 Sv of Lower Thermocline Water South of the NVJ bifurcation there is a net winter equatorward flow of 2 Sv and 6 Sv of poleward flow in summer